Teachers’ Implicit Attitudes Toward Ethnic Minority Students: A Systematic Review - Costa, Sara; Langher, Viviana; Pirchio, Sabine (Frontiers in Psychology, 2021)
Although instruments to assess implicit attitudes were introduced more than 20 years ago, still there are few studies in the field of education that use them, despite the evidence that teachers with negative implicit attitudes can negatively affect the academic performance of their students. This review aims to summarize the results of studies that investigated the relationship between implicit ethnic attitudes of teachers and achievement of students. The review was conducted according to PRISMA-statement through searches in the scientific database PsychINFO, PsycARTICLES, and ERIC. Nineteen studies were included. Results show that overall teachers (from different school levels and different countries) hold negative implicit attitudes toward ethnic minority students, which play an important role in affecting the academic path of these groups of students. This review highlights the need to continue to use implicit attitudes procedures in future researches, in order to identify those factors that may contribute to the formation and expression of implicit attitudes of teachers; and the need to increase awareness of the implicit attitudes and multicultural practices of teachers in teaching programs.